205k views
15 votes
Ax + by = a - b
bx - ay = a+ b
by elimination ​

2 Answers

12 votes
Answer: x = 1, y = -1

Explanation:

As the answer involves many steps, I’ve taken a pic of my working. Please check the attached photo.
Ax + by = a - b bx - ay = a+ b by elimination ​-example-1
User Japzdivino
by
5.5k points
5 votes


ax + by = a - b \: \: \: ...(i)\\ \\ bx - ay = a+ b \: \: \: ...(ii) \\ \\

Multiply equation (i) with a and equation (ii) with b ,


{a}^(2) x + aby = {a}^(2) - ab \: \: \: ...(iii)\\ \\ {b}^(2) x - aby = ab + {b}^(2) \: \: \: ...(iv)

Adding (iii) and (iv) , we get ,


( {a}^(2) + {b}^(2) )x = {a}^(2) + {b}^(2) \\ \\ x = 1

Now , from (i) ,


ax+by=a−b \\ \\ a+by=a−b\\ \\ by=−b \\ \\ y=−1

User Cleon
by
5.6k points